Ethylene-Inducible AP2/ERF Transcription Factor Involved in the Capsaicinoid Biosynthesis in Capsicum - Wen, Jinfen; Lv, Junheng; Zhao, Kai; Zhang, Xiang; Li, Zuosen; Zhang, Hong; Huo, Jinlong; Wan, Hongjian; Wang, Ziran; Zhu, Haishan; Deng, Minghua (Frontiers in Plant Science, 2022)
Ethylene is very important in the process of plant development and regulates the biosynthesis of many secondary metabolites. In these regulatory mechanisms, transcription factors (TFs) that mediate ethylene signals play a very important role. Capsaicinoids (CAPs) are only synthesized and accumulated in Capsicum species, causing their fruit to have a special pungent taste, which can protect against attack from herbivores and pathogens. In this study, we identified the TF CcERF2, which is induced by ethylene, and demonstrated its regulatory effect on CAPs biosynthesis. Transcriptome sequencing analysis revealed that the expression patterns of CcERF2 and multiple genes associated with CAPs biosynthesis were basically the same. The spatiotemporal expression results showed CcERF2 was preferentially expressed in the placenta of the spicy fruit. Ethylene can induce the expression of CcERF2 and CAPs biosynthesis genes (CBGs). CcERF2 gene silencing and 1-methylcyclopropene (1-MCP) and pyrazinamide (PZA) treatments caused a decrease in expression of CBGs and a sharp decrease in content of CAPs. The results indicated that CcERF2 was indeed involved in the regulation of structural genes of the CAPs biosynthetic pathway.